Late endoscopic removal of a bullet in the orbital apex - Chai, Yan Yu; Safuraa, Sharifah Intan; Kanapaty, Yogesvaran; Doi, Mohamad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
We report a case of gunshot injury causing bullet embedded in the left orbital apex via entry point at left eyebrow with immediate left visual impairment. The exact location of bullet was identified using computerized tomography scan and the bullet was removed via endoscopic approach. The case showed the management of bullet removal with endoscopic guidance to minimise the injury to adjacent structure and for better cosmetic outcome without any external incision to the face. In the current case report the bullet was removed via endoscopic approach. Endoscopic removal of bullet in the orbital apex causes less local damage, less bleeding risk , better wound healing, and better cosmetic outcomes.